Case report: mutation analysis of primary pulmonary lymphoepithelioma-like carcinoma via whole-exome sequencing - Hong Xuan (Diagnostic Pathology, 2019)
Abstract Background Primary pulmonary lymphoepithelioma-like carcinoma (LELC) is a rare tumor subtype accounting for around 0.9% of lung cancers. At present, research on LELC mainly focuses on pathological diagnosis, while the molecular mutation landscape is still unclear. Case presentation A 72-year-old female presented a productive cough for three weeks followed by severe symptoms for another week. Respiratory sounds were weak and coarser in the right lung field. F-FDG PET-CTA showed a hypermetabolic mass in the upper lobe of the right lung as well as the enlargement of right hilar and subcarinal lymph nodes. Hematoxylin-eosin staining and immunohistochemistry staining of the biopsy established the diagnosis of primary pulmonary LELC. After thoracoscopic-assisted radical resection of right lung cancer and middle lobe of right lung, the patient’s vital signs were stable without apparent productive cough, chest pain, chest tightness and other subjective discomforts. Furtherwhole exome sequencing of the patient’s tumor tissue and leukocytes (served as a germline mutation control) revealed 613 somatic gene mutations, and of which mutations in PRIM2, KCNB1, CDH1, and ATRX were most likely related to the LELC pathogenesis. The recurrence of gene mutations from various cancers database and a tumor mutation burden (TMB) of 18.7 mutations/mb were revealed as well. Conclusion Our findings have illustrated the genomic profile of a primary pulmonary LELC case and provided a positive biomarker that immune checkpoint blockade is potentially effective for this patient in further treatment.